Effect of Exclusive Breatfeeding on The Incidence of Acute Respiratory Infections - Muthoharoh, Husnul; Fajrin , Fitriana Ikhtiarinawati; Setiyarini, Anggraini (Universitas Muhammadiyah Yogyakarta, 2023)
Introduction – Acute Respiratory Infection (ARI) is a respiratory infection where the cause is a virus or bacteria that lasts for 14 days. One of the efforts to prevent ARI in infants is to provide exclusive breastfeeding, because breast milk contains elements of specific and non-specific immunity that can protect newborns from respiratory infections. Purpose – The aim of the study was to determine the effect of exclusive breastfeeding with the incidence of Acute Respiratory Infection (ARI) in infants aged 7-24 months in the Community Health Center Ujung Pangkah Gresik. Methodology/Approach – The research design used was observational analytic with a cross sectional approach. The population in this study were all infants aged 7-24 months. The number of sample 60 babies taken with the sampling technique using purposive sampling method. The study used a questionnaire with a closed ended item type of questionnaire. Data analysis used univariate and bivariate analysis using Chi Square. Findings – The results showed that 33 respondents (55 percent) had ARI and 27 respondents (45 percent) did not. Respondents who did not give exclusive breastfeeding were 28 respondents (46.7 percent), giving exclusive breastfeeding were 32 respondents (53,3 percent). This shows that the proportion of children under five who are not exclusively breastfed and has ARI is higher than the proportion of infants who are exclusively breastfed and have ARI. The results of statistical calculations obtained p-value = 0.000 (p-value <0,05), so there is a relationship between exclusive breastfeeding and the incidence of ARI in toddlers at the Ujung Pangkah Health Center. Originality/ Value/ Implication – This research is the result of my own work and has never been published at all.